The Power of Muslim Consumers: Animosity, Religion and Product Choices in Boycott Actions - S Syawaluddin; Moh Agus Nugroho; Suci Larasati; M Agus Izzi Faizin (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2026)
Purpose:This study aims to examine the factors influencing the intention of Indonesian Muslim consumers to boycott products affiliated with Israel. Specifically, the research investigates the roles of attitude toward boycott, religiosity, consumer animosity, and product judgment in shaping boycott intentions.Design/methodology:A quantitative approach was employed using a structured survey administered to 215 Muslim consumers in Indonesia, selected using purposive sampling. The measurement items were adapted from established scales in prior consumer behavior studies. Data were analyzed using PLS-SEM to examine the relationships among the study variables.Findings:The results indicate that attitude toward boycott, religiosity, and consumer animosity have a positive and significant effect on boycott intention. In contrast, product judgment negatively influences consumers’ intention to boycott Israeli-affiliated products. These findings suggest that ideological, emotional, and evaluative factors simultaneously shape consumer decision-making in politically sensitive consumption contexts.Practical implications:The study provides practical insights for companies and marketers operating in Muslim-majority markets. Firms are encouraged to conduct cultural and religious sensitivity assessments before introducing products and to develop ethical brand positioning strategies that align with Muslim consumers’ values. Understanding socio-political and religious sentiments is crucial for minimizing reputational risks in politically charged markets.Originality/Value:This research contributes to the literature on value-driven consumer behavior by exploring how global political issues and religious values influence boycott intentions. It highlights the interplay between ideological conviction and consumer decision-making, and calls for further investigation into the roles of social media and social norms in shaping ethical consumption among Muslim consumers.